Evaluación de la Coriodermina en pacientes con Psoriasis Vulgar - Cuervo, Dalia (Universidad y Salud, 2007)
The therapeutic effectiveness of coriodermina jelly and placebo was evaluated comparing them with a positive control: cream of hydrocortisone, it has been applied topically in ambulatory patiens with histologic and clinical diagnosis of psoriasis. We undertook a phase III, prospective and randomised trial, this eassy was double-blind for patiens whom received coriodermina jelly and placebo, and opened for the group that received cream of Hydrocortisone. 18 paients were included, they were distributed in three groups with the same amount each one, they were coming from the special consultation of Psoriasis from the Hospital Clínico Quirúrgico “Hermanos Ameijeiras”. The evaluation of the clinical response was measure by the Psoriasis, Area and Severity Index (PASI) during the first six months of treatment. We found thar coriodermina jelly has a benefical effect in patients with Psoriasis and no adverse reactions were presented with the use of the medication in study.